Assessment of the nutritional composition of breakfast cereal and the nutritional benefits of two serving portions for young children - AbuKhader, Majed M (Progress in Nutrition, 2017)
Background: Breakfast cereal is a widely popular morning breakfast meal and it is a source of nutrients and fibers for both children and adults. Purpose: this study was conducted to assess the nutritional composition of selected breakfast cereals in Omani market and the nutritional benefits of two serving portions; 30g and 45g. Methods: The nutritional information was extracted from the nutrition panel of each 26 products collected from hypermarket outlets and statistically analysed. Results: The salt content was found to be significantly high (P = 0.015) with original/plain and other flavours cereals when compared with the other two groups; honey/sugar coated and chocolate flavour cereals. For the 26 breakfast cereals products, the serving portion of 45g has significant amounts of nutrients, except for total fat, when compared with that of 30g portion. The assessment of nutritional benefits of 30g and 45g portions in terms of total carbohydrates for two age groups 4-8 years and 9-13 years old children respectively is found to be within the range of recommended breakfast intake of carbohydrates per day. On the other hand, the energy intake provided by both portions for both age groups is low and inadequate when compared to the recommended breakfast intake of energy per day. Conclusion: For some breakfast cereal products the consumption by young children should be monitored due to the high salt content. In the studied sample, energy intake from 30g and 45g portions is considered low and should be compensated by the consumption of energy-rich food sources such as biscuits and nuts.